Letter: how can we reduce mortality in elderly patients with acute severe ulcerative colitis? Authors' reply. Issue 12 (23rd May 2020) - Dong, Catherine; Metzger, Marie; Holsbø, Einar E.; Perduca, Vittorio; Carbonnel, Franck
Abstract : LINKED CONTENT This article is linked to Dong et al and Li et al papers. To view these articles, visit https://doi.org/10.1111/apt.15592 and https://doi.org/10.1111/apt.15702 .